2020
DOI: 10.1136/ijgc-2019-001178
|View full text |Cite
|
Sign up to set email alerts
|

Palliative electrochemotherapy in primary or recurrent vulvar cancer

Abstract: ObjectiveSince vulvar cancer is such a rare disease, the international experience with electrochemotherapy has been derived from only a few centers. The aim of this study was to evaluate clinical outcome and side effects profile with the use of electrochemotherapy in patients with primary or recurrent vulvar cancer.MethodsData were retrospectively collected from November 2017 to November 2019 in two major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Based on the ECT efficacy in the palliative treatment of skin metastasis, our group published in 2013 the first results on ECT in VC reporting with high local control rates (80%) and significant symptoms improvement [ 6 ]. Subsequently, other groups confirmed our results [ 7 , 39 ]. The most frequently treated histologic type was SCC, but data on few cases of melanoma and vulvar Paget’s disease were also promising.…”
Section: Principles Of Electrochemotherapy and The New Palliative Care In Vulvar Cancersupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the ECT efficacy in the palliative treatment of skin metastasis, our group published in 2013 the first results on ECT in VC reporting with high local control rates (80%) and significant symptoms improvement [ 6 ]. Subsequently, other groups confirmed our results [ 7 , 39 ]. The most frequently treated histologic type was SCC, but data on few cases of melanoma and vulvar Paget’s disease were also promising.…”
Section: Principles Of Electrochemotherapy and The New Palliative Care In Vulvar Cancersupporting
confidence: 90%
“…Unfortunately, even surgery and chemotherapy often do not meet this need. In this scenario, some research groups have proposed electrochemotherapy (ECT) to achieve local tumor control and symptoms relief based on the positive results recorded in skin tumors [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Survival after one year in this population was observed at 50%. Electrochemotherapy may have a role in the management of vulvar cancer, especially as a palliative treatment when other therapies are no longer applicable [291]. However, technical issues mean that this tool is sporadically applied.…”
Section: Advancements In Vc Therapy Based On Better Profiling and Novmentioning
confidence: 99%
“…However, technical issues mean that this tool is sporadically applied. Conversely, CAP has received much more attention from researchers due to its ability to specifically induce the selective death of cancer cells over normal healthy cells, called antitumour selectivity [291][292][293], by activating the apoptosis of these cells, decreasing their proliferation and mobility, and by recovering their sensitivity to therapeutic drugs. Previous studies showed encouraging results where CAP returned cisplatin-resistant ovarian cancer cells [75], paclitaxel-resistant breast cancer cells [158], tamoxifen-resistant breast cancer cells [39], and temozolomide-resistant malignant glioma cells [294] to a drug-sensitive state, in addition to inducing apoptosis and growth inhibition.…”
Section: Advancements In Vc Therapy Based On Better Profiling and Novmentioning
confidence: 99%
“…The first clinical trial of electroporation in combination with chemotherapy (electrochemotherapy 'ECT') was performed in 1991 [3]. It has since been tested in clinical trials for treatment of vulval cancer [4,5], nonmelanoma skin cancer [6], cutaneous metastases [7,8] and tumours in internal organs [9,10]. When treated with ECT, tumour cells are selectively more sensitive than normal cells in vitro [11,12], thus preserving healthy tissue.…”
Section: Introductionmentioning
confidence: 99%